Cradle-to-gate life cycle assessment of beneficiated phosphate rock production in Tunisia - Roukaya Issaoui; Christine Rösch; Jörg Woidasky; Mario Schmidt; Tobias Viere (Sustainability Management Forum, 2022)
To improve the sustainable management of phosphorus, numerous LCA studies, using primary data, have been conducted for phosphorus recovery technologies from wastewater, but not for phosphate rock mining.This article addresses this issue by conducting a~cradle to gate assessment of beneficiated phosphate rock production using primary data. This study aims to share an updated Life Cycle Inventory dataset of beneficiated phosphate rock production.The studied system is the open-pit mining operations and the wet beneficiation process located in the south of Tunisia. The functional unit is 1 kg of P2O5. Twelve environmental impact categories were assessed using the ReCiPe Midpoint method.The results of Life Cycle Inventory show that the average loss of phosphorus between mining operations, mechanical preparation, and the wet beneficiation is 0.3 kg of P2O5 per 1 kg P2O5. The losses occur mainly during the scrubbing and hydrocycloning. Compared to the production system in Florida, USA, according to the Ecoinvent database 3.4, the production of 1 kg P2O5 in Tunisia has higher Global Warming Potenzial, higher water depletion potential, higher PM10 emission, Photochemical oxidant formation, soil pollution potential, and human toxicity potential.In conclusion, primary data shows comparable results to the generic Life cycle Inventory of wet beneficiation phosphate rock in the Ecoinvent database. This study contributes to enlarge data about sedimentary phosphate rock extraction and beneficiation globally as currently only the USA and Morocco were reported in databases.
Keywords: 650; Life Cycle Assessment; Phosphate rock mining; Life Cycle Inventory; Environmental impacts